How do tutors use data to support their students?. (2nd January 2019) - Walker, Steve; Olney, Tom; Wood, Carlton; Clarke, Anactoria; Dunworth, Moira
ABSTRACT: Despite widespread enthusiasm, evidence of the effectiveness of learning analytics remains mixed. One possible explanation for this is that insufficient attention has been paid to the contexts in which it is introduced. We report here on a small-scale study into the prior use of data and communications technologies by tutors, who comprise a key user group in The Open University's tuition model. Tutors interviewed reported using a complex set of data sources and information tools, and creating local/personal tools and methods for keeping track of students and their interactions with them.